2020
DOI: 10.1002/ppul.25078
|View full text |Cite
|
Sign up to set email alerts
|

Home nursing for children with home mechanical ventilation in the United States: Key informant perspectives

Abstract: Objectives & Hypothesis Children with home mechanical ventilation (HMV) require skilled care by trained caregivers, and their families feel the impacts of ubiquitous home nursing shortages. It is unknown which factors determine allocation; no standards for private duty nursing intensity exist. We sought to characterize provider experiences with and opinions on home nursing for children with HMV, hypothesizing providers would describe frequent home nursing gaps across clinical scenarios. Methods Purposeful and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
0
13
0
5
Order By: Relevance
“…Typically, private duty nursing coverage is required during the first two weeks of being home. However, due to the recent national shortage of availability of skilled home nurses ( 37 ), parents are encouraged to rely on additional caregivers including family, relatives, and friends to provide respite care. A published quality improvement project reported that using a standardized discharge process that included educational materials, a chronic ventilation road map for caregivers, electronic tracking of discharge readiness, team-based care coordination, and timely arrangement for home nursing significantly decreased the length of hospital stay and cut the cost of hospitalization without compromising the safety of ventilator-dependent children with tracheostomy discharged to home ( 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, private duty nursing coverage is required during the first two weeks of being home. However, due to the recent national shortage of availability of skilled home nurses ( 37 ), parents are encouraged to rely on additional caregivers including family, relatives, and friends to provide respite care. A published quality improvement project reported that using a standardized discharge process that included educational materials, a chronic ventilation road map for caregivers, electronic tracking of discharge readiness, team-based care coordination, and timely arrangement for home nursing significantly decreased the length of hospital stay and cut the cost of hospitalization without compromising the safety of ventilator-dependent children with tracheostomy discharged to home ( 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the QT met the parents' and nurses' perceived need for nursing hours 56% and 42% of the time, there was still a significant perceived need for more nursing hours by both groups. A published report identified that physicians and nurses believed families with children on home mechanical ventilation should receive more nursing hours, at least during the transition to home (Sobotka et al, 2020). A Midwest study on children receiving palliative home care nursing found a 40-hour-per-week difference between allotted versus received hours and attributed this to a home care nursing shortage (Weaver et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Models, frameworks and principles of care have been developed to support integration of care ( 3 , 12 ) however, despite an increase in initiatives in this area it is insufficient to meet the needs of these children. There is continuous evidence internationally that many children with complex needs have ongoing issues with access to appropriate and continuous care in the home, access to respite care services, and challenges in communication within and across services ( 13 16 ). There is also continuous reference to the need for a care coordinator in the community to support the integration of their care needs ( 9 , 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%